Giới hạn \(\lim\limits_{x\to-\infty}\left(\sqrt{x^2+1}-\sqrt{9x^2+2x}\right)\) bằng
\(-2\) | |
\(-\infty\) | |
\(+\infty\) | |
Không tồn tại |
Chọn phương án B.
\(\begin{aligned}
&\lim\limits_{x\to-\infty}\left(\sqrt{x^2+1}-\sqrt{9x^2+2x}\right)\\ =&\lim\limits_{x\to-\infty}\left(-x\sqrt{1+\dfrac{1}{x^2}}+x\sqrt{9+\dfrac{2}{x}}\right)\\
=&\lim\limits_{x\to-\infty}x\left(-\sqrt{1+\dfrac{1}{x^2}}+\sqrt{9+\dfrac{2}{x}}\right)\\
=&-\infty.
\end{aligned}\)
Vì \(\begin{cases}
\lim\limits_{x\to-\infty}x=-\infty\\
\lim\limits_{x\to-\infty}\left(-\sqrt{1+\dfrac{1}{x^2}}+\sqrt{9+\dfrac{2}{x}}\right)=2>0
\end{cases}\)